Prospects and opportunities for mussel Mytilus trossulus farming in the southern Baltic Sea (the Gulf of Gdańsk) - Sokołowski Adam; Lasota Rafał; Alias Izabela Sami; Piłczyńska Joanna; Wołowicz Maciej (Oceanological and Hydrobiological Studies)
In the Baltic Sea, where osmotic stress limits the growth of marine organisms, mariculture is driven primarily by the need to improve the status of the environment. To this end, several mussel farms have been attempted in selected areas, except the southern Baltic. The pilot culture of Mytilus trossulus was carried out with the use of a modified long-line system in the Gulf of Gdańsk in 2009–2012, providing the first evaluation of the mussel farming potential in this area. The growth rate of mussels (3.0–6.7 mm year−1) in the gulf was in the low range, but the mean wet biomass gain (1.50 kg m−1 normalized culture rope) was among the highest in the Baltic. After a two-year growth period, one tonne of mussels fixed in their soft tissues from 93 to 98 kg N t−1 and 11 kg P t−1. The cost-benefit analysis revealed a negative budget balance of production for human consumption, with a total income covering only 12.0% of the cumulative costs. Mussel farming in the gulf can therefore only be justified to improve the environmental quality if additional funding mechanisms are put in place to support farming activity.